On the Smith normal form of a skew-symmetric D-optimal design of order n≡2 (mod4) - Greaves, Gary Royden Watson (2021)
We show that the Smith normal form of a skew‐symmetric D‐optimal design of order n≡2 (mod 4) is determined by its order. Furthermore, we show that the Smith normal form of such a design can be written explicitly in terms of the order n, thereby proving a recent conjecture of Armario. We apply our result to show that certain D‐optimal designs of order n≡2(mod 4)are not equivalent to any skew‐symmetric D‐optimal design. We also provide a correction to a result in the literature on the Smith normal form of D‐optimal designs.